2008
DOI: 10.1021/ol801168j
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Synthesis of 3,3-Disubstituted Oxindoles through Pd-Catalyzed Cyanoamidation

Abstract: The first enantioselective cyanoamidation of olefins provides quick access to a variety of 3,3-disubstituted oxindoles. The combination of Pd(dba)2, an optically active phosphoramidite, and N, N-dimethylpropylene urea (DMPU) in decalin were found to be the best conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 187 publications
(74 citation statements)
references
References 37 publications
0
71
0
3
Order By: Relevance
“…[459] Das Cyano- Die erste erfolgreiche Anwendung eines PhosphoramiditSilberkomplexes wurde ebenfalls erst kürzlich beschrieben. [460] Dabei wurden durch silberkatalysierte 1,3-dipolare Cycloaddition der arylsubstituierten Iminoglycinate 338 mit aktivierten Alkenen wie tert-Butylacrylat (339) [461] die Prolinderivate 340 erhalten.…”
Section: Palladiumkatalysierte Cyanoamidierungunclassified
“…[459] Das Cyano- Die erste erfolgreiche Anwendung eines PhosphoramiditSilberkomplexes wurde ebenfalls erst kürzlich beschrieben. [460] Dabei wurden durch silberkatalysierte 1,3-dipolare Cycloaddition der arylsubstituierten Iminoglycinate 338 mit aktivierten Alkenen wie tert-Butylacrylat (339) [461] die Prolinderivate 340 erhalten.…”
Section: Palladiumkatalysierte Cyanoamidierungunclassified
“…2 烯丙基取代的氰醇化合物以及 α-胺基腈在 非金属催化的分子内碳氰化反应中的应用 过渡金属催化的烯烃及炔烃的分子内氰官能团化 反应是一类重要的碳碳键形成反应, 也是制备官能团化 腈类化合物最有效和便捷的方法之一 [15] . 该类反应通 …”
Section: α-胺基腈与unclassified
“…Phosphoramidites L9, 37 L11, 38 L12, 39 and L13 40 derived from dimethyl BINOL, biphenol, spirobiindane diol, and TADDOL, respectively, unexpectedly resulted in higher reactivity than L8 but poorer selectivity (entries 9, 11-13). Bisphosphorus ligands L14, L15, 41 and L16 42 gave poor conversion and selectivity (entries [14][15][16]. The effects of solvents and additives were examined with using 2 mol % Pd(dba) 2 and 8 mol % phosphoramidite L8 (Table 5).…”
Section: Enantioselective Synthesis Of 33-disubstituted Oxindolesmentioning
confidence: 99%
“…15 Replacement of the alkyne with an alkene led to the formation of a,a-disubstituted lactams: a palladium-catalyzed Heck-type reaction proceeded from alkenyl chloroformamides to give a-vinyl lactams. 16 As part of these studies, the reaction of alkenyl cyanoformamides with palladium catalyst was found to give a-cyanomethyl lactams. This reaction was applied to the synthesis of 3,3-disubstituted oxindoles and other a,a-disubstituted lactams and was expanded to enantioselective transformation.…”
Section: Introductionmentioning
confidence: 99%